Parameter Identification of Induction Motor Considering Soft Starter Characteristics - Pooreum Jang; Young-Su Noh; Byong Jo Hyon; Joon Sung Park; Jin-Hong Kim (IEEE Access)
In this paper, a method for estimating induction motor (IM) parameters using a soft starter has been proposed. Unlike the conventional method using a three phase inverter, the proposed method use only the soft starter to obtain IM parameters. The stator resistance, stator inductance and magnetizing inductance of the IM are estimated under the assumption of steady state because the IM connected to the grid is often used where the load torque does not change rapidly. Four quantities are defined based on currents and voltages of motor, and the angle of the rotor flux is estimated using these quantities to obtain the stator inductance and magnetizing inductance. Using the parameters obtained in this way, it is possible to estimate rotor resistance using existing methods. The effectiveness of proposed method was verified through simulations and experiments.